2005
DOI: 10.1111/j.1365-294x.2005.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of vegetative growth and gene flow in Rhizopogon vinicolor and R. vesiculosus (Boletales, Basidiomycota)

Abstract: We have collected sporocarps and tuberculate ectomycorrhizae of both Rhizopogon vinicolor and Rhizopogon vesiculosus from three 50 x 100 m plots located at Mary's Peak in the Oregon Coast Range (USA); linear map distances between plots ranged from c. 1 km to c. 5.5 km. Six and seven previously developed microsatellite markers were used to map the approximate size and distribution of R. vinicolor and R. vesiculosus genets, respectively. Genetic structure within plots was analysed using spatial autocorrelation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
6
68
0
Order By: Relevance
“…Previous studies in a DF forest, comprised of 40-to 80-year-old trees, reported higher frequencies of R. vesiculosus tubercules per unit area compared with R. vinicolor and a greater number of R. vinicolor genotypes per unit area compared with R. vesiculosus (Kretzer et al 2005;Dunham et al 2013). In our study, the number of R. vesiculosus tubercules varied among plots, and R. vinicolor accounted for the majority of tubercules encountered in five out of 12 plots.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Previous studies in a DF forest, comprised of 40-to 80-year-old trees, reported higher frequencies of R. vesiculosus tubercules per unit area compared with R. vinicolor and a greater number of R. vinicolor genotypes per unit area compared with R. vesiculosus (Kretzer et al 2005;Dunham et al 2013). In our study, the number of R. vesiculosus tubercules varied among plots, and R. vinicolor accounted for the majority of tubercules encountered in five out of 12 plots.…”
Section: Discussionsupporting
confidence: 50%
“…We predicted that a change in the number or relative abundance of R. vesiculosus and R. vinicolor tubercules and genotypes would not be related to a change in the percent of DF seedlings, saplings and/or trees <50 years old. We based this prediction on previous studies showing that R. vesiculosus consistently had more tubercules than R. vinicolor, R. vinicolor consistently had more genotypes than R. vesiculosus, and both species associated with roots from DF of all ages (Kretzer et al 2005;Beiler et al 2010;Dunham et al 2013). …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A search for variable microsatellite loci in the mushroom Laccaria laccata isolated only 5 loci, 2 of which were imperfect and each displaying only 3-6 alleles (Wadud et al 2006). Nevertheless, several investigations have used fungal microsatellite loci to differentiate fungal genets and discern some population level patterns (Kretzer et al 2003(Kretzer et al , 2005, and there are those who argue that the potential to develop informative microsatellite loci across the fungi is promising (Lim et al 2004).…”
mentioning
confidence: 99%